2018
DOI: 10.1016/j.bbadis.2017.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the generation of bioengineered bile ducts

Abstract: The generation of bioengineered biliary tissue could contribute to the management of some of the most impactful cholangiopathies associated with liver transplantation, such as biliary atresia or ischemic cholangiopathy. Recent advances in tissue engineering and in vitro cholangiocyte culture have made the achievement of this goal possible. Here we provide an overview of these developments and review the progress towards the generation and transplantation of bioengineered bile ducts. This article is part of a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
(110 reference statements)
0
17
0
1
Order By: Relevance
“…With the availability of eBD biopsies collected during liver transplantation, we embarked on characterizing organoids from the extrahepatic biliary epithelium (eBD) and compared them to paired organoids initiated from iBD of the same donor. The non-canonical Wnt-stimulated extrahepatic cholangiocyte organoids as described by Sampaziotis 16 , isolated from eBD are potent cells for regenerative medicine applications 26 , 27 . However, these cholangiocyte organoids are assumedly derived from mature primary cholangiocytes (not stem/progenitor cells) and are not dependent on canonical Wnt signaling like the LGR5-positive ICO 14 and ECO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the availability of eBD biopsies collected during liver transplantation, we embarked on characterizing organoids from the extrahepatic biliary epithelium (eBD) and compared them to paired organoids initiated from iBD of the same donor. The non-canonical Wnt-stimulated extrahepatic cholangiocyte organoids as described by Sampaziotis 16 , isolated from eBD are potent cells for regenerative medicine applications 26 , 27 . However, these cholangiocyte organoids are assumedly derived from mature primary cholangiocytes (not stem/progenitor cells) and are not dependent on canonical Wnt signaling like the LGR5-positive ICO 14 and ECO.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an earlier study on TROP2 in eBD reported that though TROP2 is non expressed in peribiliary glands, upon damage of the bile ducts TROP2 is clearly upregulated in these glands epithelial cells 31 . Although novel culture techniques provide evidence for long-term expansion of primary hepatocytes 32 , 33 and primary cholangiocytes 26 , 27 , both cell types remain challenging to maintain in culture while keeping their mature functions 13 , 14 , 28 . Expansion of ECO could provide in this shortcoming.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6) Most in vitro research on biliary physiology and pathology, however, uses cells either cultured in two-dimensional (2D) monolayers or as organoids in three-dimensional (3D) extracellular matrix (ECM). (7)(8)(9)(10)(11) These conventional methods fail to replicate many key aspects of bile duct structural organization or to recapitulate important tissue-level integrated physiological functions, such as forming a protective barrier and compartmentalizing bile.…”
mentioning
confidence: 99%
“…First the ductal ECM is generated using a variety of fabrication methods, such as rolling of a polymeric sheet, moulding, 3D printing, electrospinning and freeze-drying from synthetic or biological materials or through tissue decellularisation. 126 Subsequently, the matrices are populated with cells, generating bioengineered bile ducts. These ducts can be connected to bioreactors, which allow independent access to the luminal and extraluminal side of the construct and enable luminal flow of media without the challenge of small volume perfusates (Fig.…”
Section: Scaffolded Bioengineered Tissuementioning
confidence: 99%